2018
DOI: 10.24836/es.v28i51.509
|View full text |Cite
|
Sign up to set email alerts
|

Agroecología, instrumento para la gestión del turismo rural en Quintana Roo

Abstract: Objetivo: valorar cómo la agroecología permite la integración de actividades socioeconómicas en el espacio rural, dando cuenta de un diseño sustentable de desarrollo. Metodología: se abordan las discusiones actuales sobre lo rural y se analiza la definición del turismo rural. Resultados: uno resultado sustantivo es el análisis de la utilidad de la agroecología para generar un desarrollo endógeno y local en el espacio rural de Quintana Roo; en el que se integran patrimonios tangibles e intangibles en el desenvo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The results of Rivera-Hernández [142], Díaz-Pompa et al [143], and Cardoso-Cabrera et al [144] constitute references, as well as the specific applications reported by Fresneda and coworkers [145][146][147][148][149] in contexts similar to those analyzed in this paper, in relation to community-based tourism.…”
Section: Discussionsupporting
confidence: 74%
“…The results of Rivera-Hernández [142], Díaz-Pompa et al [143], and Cardoso-Cabrera et al [144] constitute references, as well as the specific applications reported by Fresneda and coworkers [145][146][147][148][149] in contexts similar to those analyzed in this paper, in relation to community-based tourism.…”
Section: Discussionsupporting
confidence: 74%
“…Agroecological management is one of the more maintainable agricultural systems under all of the aspects and intends to rescue the farmers' human dignity that tamed plants and animals throughout history and maintained great part of the genetic diversity used by the human species [5]. Characterised by cultural practices as rotation, consortium, organic manuring, reuse of vegetable remains, planting of repellent plants, production of bio-pesticides, exemption of pesticides and other inorganic inputs [6]. It was known that there could be many genetic and environmental effects on the yield [7].…”
Section: Introductionmentioning
confidence: 99%